PREVALENCE OF HELMINTH PARASITES IN GOATS OF NAGPUR REGION (MAHARASHTRA) - Bagde, Varsha; Maske, D K; Jumde, Pratibha; Shende, Kavita; Bansod, Shradha (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Prevalence studies of Helminth Parasites in Goats of Nagpur region of Maharashtra was carried out for a period of one year .A total of 1500 faecal samples of goats were examined in 10 villages from different localities viz., Ramtek and Katol Tahsils of Nagpur district of Maharashtra. A total of 904 (60.26%) samples were found positive for different helminthic infections. Nematode infection was most commonly encountered during and after rainy season. Only 204 (22.56%) cases were found positive for mixed helminthic infection, out of which, the most common cases of mixed infection were of Strongyloid sp, Trichuris sp. and Moniezia sp.
Keywords: Goat; Helminth Parasites; Prevalence